Pembelajaran Missouri Mathematics Project dan Penemuan Terbimbing terhadap Hasil Belajar Matematika Ditinjau dari Kemampuan Awal di SMK - istiqomah subagya (Jurnal VARIDIKA, 2016)
The aims of this study are to test: 1) the differences of the influences between MMP learning strategy and Guided Discovery learning strategy towards mathematics learning outcomes, 2) the differences of the influences between students’ initial ability level towards mathematics learning outcomes, and 3) the interaction between MMP learning strategy and students’ initial ability level towards mathematics learning outcomes. The Quasi-experimental research design used the population of all students from class XI of SMKN 3 Klaten. This research uses cluster sampling. Data were collected by documentation and tests. Technical analysis used anava, different two way cells, and then followed by Scheffe method. The results of this study showed: 1) the students’ learning outcomes by using MMP learning strategy are better than by guided discovery learning strategy, 2) the students’ learning outcomes of high initial ability level students is better than middle and low initial ability level students, and the students’ learning outcomes of middle initial ability level students is better than low initial ability level students, and 3) MMP learning strategy is more effective than guided discovery learning strategy towards middle initial ability level students. MMP learning strategy, the learning outcomes of high initial ability level students is better than middle and low initial ability level students, the learning outcomes of middle initial ability level students is better than low initial ability level students. Meanwhile, guided discovery learning strategy, the learning outcomes of high initial ability level students is better than middle and low initial ability level students. As for,  in guided discovery learning strategy, the learning outcomes between middle and low initial ability level students gets the same learning outcomes.